Yes-associated protein-based detection of acute type A aortic dissection and evaluation of therapeutic responses - Zhu, Kai; Li, Hao-Xi; Wu, Dong-Dong; Qian, Si-Chong; Wang, Xiao-Long; Li, Jian-Rong; Jiang, Wen-Jian; Liu, Hong; Li, Hai-Yang; Zhang, Hong-Jia (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAcute aortic dissection is a lethal cardiovascular emergency; early diagnosis is critically necessary. Novel serum biomarkers can potentially help in early detection and estimation of postoperative outcomes. Yes-associated protein (YAP) is a critical effector of the Hippo pathway, our aim was to explore the association between YAP and the diagnosis and prognosis of AD.MethodsWe prospectively recruited 110 consecutive chest-pain patients [acute type A aortic dissection (ATAAD), n = 60; acute coronary syndrome (ACS), n = 50]. Blood samples were collected to determine levels of YAP and other serum biomarkers, and receiver operating characteristic curves (ROC) were constructed to assess the predictability in early diagnosis of AAD and postoperative major adverse events (MAEs).ResultsYAP concentration was substantially elevated among ATAAD patients [3.45 (3.18, 3.63) vs. 2.44 (2.23, 2.59), P < 0.01]. Moreover, the white blood cell (WBC) count and plasma fibrin D-dimers were remarkably high among ATAAD patients [11.46 (9.57, 14.03) vs. 6.24 (5.10, 7.30), P < 0.01; 2,097.00 (998.75, 3,652.00) vs. 97.00 (67.25, 137.00), P < 0.01]. The serum YAP level held as a good predictive value in early diagnosis of ATAAD. The optimal cutoff value was 3.15 ng/ml, with an AUC of 0.94 (95% CI, 0.90–0.98, P < 0.01), sensitivity of 80% and specificity of 98%. The combined model of YAP, WBC count and D-Dimer exhibited an enhanced predictive power, with an AUC of 0.99 (95% CI, 0.98–1.00, P < 0.01). Serum YAP values at 12 h post-surgery provided the most accurate prediction of postoperative MAEs, with an optimal cutoff value of 3.60 ng/ml, an AUC of 0.89 (95% CI, 0.79–0.99, P < 0.01), and sensitivity and specificity of 88% and 82%, respectively.ConclusionsThe serum YAP concentration is an early and sensitive serum bioindicator for distinguishing AAD from ACS. Moreover, the amount of postoperative circulating YAP is a robust indicator of postoperative MAEs.